Alginate wrapped NiO-ZnO Nanocomposites-based Catalysts for Water Treatment - Abakar, Mohamed (Journal of King Abdulaziz University: Science, 2024)
In this paper, nickel oxide-zinc oxide (NiO-ZnO) nano-catalyst was embedded in an alginate polymer (Na alg/NiO-ZnO), a nanocomposite that was used as a nano-catalyst for catalytic conversion of deleterious contaminants such as organic dyes (Acridine Orange “ArO”, Methylene Blue “MB”, Methyl Orange “MO”, Congo Red “CR”) and 4-Nitrophenol “4-NP” as well. Photocatalytic degradation was found to be more efficient for ArO, however catalytic reduction of MB was the best among all contaminants. FESEM, EDS, XRD and FTIR techniques were used to identify the shape and structure of the nanomaterial (Na alg/NiO-ZnO). Reduction percentage of MB was assessed to be 95.25 % in just 13 minutes, whereas ArO has been photo-catalytically degraded up to 77.5 % in 150 minutes. Furthermore, the catalytic property of Na alg/NiO-ZnO in the reduction of organic dyes was investigated using various catalyst amounts, dye types, reaction times, and reducing agent dosages at room temperature (rt). Solar light helped photo-degradation and NaBH4 assisted reduction of organic dyes, as water pollutants, were studied using Na alg/NiO-ZnO